Wheel/Rail Tangential Contact Stress Evaluation by Means Of the Modified Strip Method - Tomas Lack; Juraj Gerlici (Communications - Scientific letters of the University of Zilina, 2014)
The article deals with the way of calculating tangential stresses over non-elliptical contact patch where Kalker’s simplified method FASTSIM can be used advantageously. This method named FASTSTRIP is adapted for non-elliptical contact area calculated by means of the Strip method. This method is almost as quick as FASTSIM and the results are similar to the CONTACT results. This method may be useful for rail vehicles in track dynamics computation.